ปัจจัยที่มีผลต่อการเปลี่ยนแปลงผู้สอบบัญชี : การศึกษาเชิงประจักษ์ในตลาดหลักทรัพย์แห่งประเทศไทย - กชกร ตรังวัชรกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The objectives of this research are to study about determinants of auditor changes of the listed companies in the stock Exchange of Thailand as auditor change since 2544-2546, and to study for which determinants are relative with the most auditor changes. This research is an empirical study by collecting secondary data since 2544-2546 from audit reports, financial statements, financial statement remarks, and any documents to which are related the listed companies in the stock Exchange of Thailand. This study was emphasized to seek the relative between any determinants as result to auditor change and auditor change, which determinants are relative with auditor change. As a result of the study, change in board of company has an essential relative with auditor change because of an authority of board in an appointment of auditor. Such as, the new auditor may be appointed in place of the former one due to change in board. As a suggestion for auditor, the study inform that other factors, such as an auditor report about scope limited, disputes in accounting policies between auditor and company, uncertainty in going concern and other uncertainty beside of going concern, are not relative with auditor change. Therefore, auditors should be honestly in performing their work and report their opinions without no concerns about anything.